Bibliometric Analysis: Trends in the Last 10 Years of EPA Method Implementation (Exploration, Introduction, and Application of Concepts) in Education - Azizah, Nur; Fajar, Muhammad; Rahmati, Pramita Dwi; Annur, Syubhan; Sya'ban, Muhammad Fuad (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This research aims to investigate research trends in the implementation of the EPA Method (Exploration, Introduction, and Application of Concepts) through bibliometric analysis based on the Google Scholar (GS) database in the field of education over the last 10 years. The database was reviewed using Harzing's Publish or Perish on October 14, 2024. The method used was a quantitative method with a descriptive bibliometric approach. The results of the bibliometric analysis show a significant increase in the number of publications examining this method in the last 10 years, with varying increases each year, indicating high academic interest in approaches to exploration, introduction, and application of the concept. In addition, visual analysis using VOS viewer shows a map of the relationships between various terms related to the EPA Method. The increasing number of publications and academic attention shows that the exploration, introduction, and application of concept approaches are relevant to today's educational needs. Therefore, researchers and educational practitioners are expected to utilize these findings to design more effective, innovative, and contextual learning strategies according to the characteristics of learners.